A Political-Economic Model of the Choice of Exchange Rate Regime - Sun, Yan (IMF Working Papers; Working Paper ;, 2002)
Facing electoral uncertainty, a government chooses its exchange regime in a trade-off among three incentives: (i) tying the hands of its opponent should it lose the election; (ii) facilitating its own future policy implementation should it win the election; and (iii) increasing its chance of reelection.